Pelatihan Penyusunan Laporan Keuangan bagi UKM Batik Kampung Tematik di Kelurahan Mangunharjo Kecamatan Tembalang - Tri Rinawati; Asih Niati; Teguh Ariefiantoro (Universitas Muhammadiyah Semarang, 2021)
One of the thematic villages in Tembalang sub-district is Mangunharjo Village with the name Durenan Indah Thematic Village which was built based on existing activities in the RW 06 area namely UKM